Early growth and nodulation of Leucaena and Gliricidia and the effects of pruning on biomass productivity - Ezenwa, I.V.; Atta-Krah, A.N. (Wiley, 1992)
Patterns of early root and shoot growth and nodulation, and the effects of increasing frequency of pruning on leaf dry-matter yield, root dry weight and nodulation of Leucaena leucocephala and Gliricidia sepium were studied in two pot experiments. In G. sepium the emphasis during early growth was on the production of lateral roots and nodulation; in L. leucocephala it was on the elongation of the tap root. This may have been the cause of delayed nodulation in L. leucocephala as the lateral roots were observed only at 12 weeks after planting. Increasing the frequency of pruning from 12-week to 4-week intervals significantly reduced leaf and root dry-matter yields and nodulation in both species. The highest leaf dry-matter yields were produced with 8-weekly and 12-weekly pruning regimes, while the highest root weight was produced by the uncut plants. For all nodulation parameters measured, uncut plants performed better than plants cut every 4 weeks, but were inferior to those cut every 8 weeks which, in turn, were inferior to those cut every 12 weeks, indicating that a lenient pruning regime may enhance nodulation and/or nodule longevity.